Interaksi Aktor Dalam Pelaksanaan Kebijakan Pemerintah Daerah Terkait Penggunaan Dana Desa Di Kabupaten Garut - Yanhar Jamaluddin (Jurnal Administrasi Publik dan Pembanguan, 2019)
This article was compiled against the ineffectiveness of actors' interactions in the implementation of Regional Government policies related to the use of Village Funds in Garut Regency, West Java Province to achieve the expected goals, especially to realize a prosperous Village community. This article is intended to analyze why the interaction of actors in the implementation of Regional Government policies related to the use of Village Funds has not been effective. Research uses a qualitative approach and descriptive method, with individual analysis units. Data collection through library studies, participatory observation, and unstructured interviews. While data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions or verification. The results of the discussion found that; The interaction between village heads and TPKs has not been oriented towards achieving common goals effectively because collaboration between implementing actors is dominated by the authority of the village head and is less based on the principles of transparency and accountability. Based on these findings, it is recommended that to streamline the interaction of actors in the implementation of Local Government Policies related to the use of Village Funds in Garut Regency, Village Heads and TPKs need to develop a pattern of teamwork oriented towards a common goal based on collective awareness and responsibility, as well as developing principles of transparency and accountability.